The Influence of Experience Quality and Destination Image on The Behavioral Intentions of Lagundri Beach Tourists with Satisfaction as a Mediation - Paskalis Dakhi (Westscience Press, 2024)
The current development of the tourism business is changing human lifestyles, especially in enjoying life and using free time with recreational activities. This research explores the relationship between the quality of experience obtained by tourists at Lagundri Beach and their intention to behave again, with satisfaction acting as a potential mediator. Through a quantitative approach and the use of questionnaires as a data collection tool from a sample of 156 people, this research seeks to fill the gap in understanding of the factors that influence tourists' behavioral intentions to return to this destination, especially the quality of experience and mediated by satisfaction. The results of the analysis show that the quality of experience enjoyed by tourists at Lagundri Beach has a significant influence on their level of satisfaction. Not only that, satisfaction also turns out to be a significant mediating factor in the relationship between the quality of experience and tourists' behavioral intentions to return. These findings not only provide important insights for the tourism industry in its efforts to improve the tourist experience at Lagundri Beach, but also provide a theoretical contribution in understanding the dynamics of tourist behavior and its influence on future travel decisions.